2022
DOI: 10.3389/fbioe.2022.1033450
|View full text |Cite
|
Sign up to set email alerts
|

Shear-driven modelling of thrombus formation in type B aortic dissection

Abstract: Background: Type B aortic dissection (TBAD) is a dangerous pathological condition with a high mortality rate. TBAD is initiated by an intimal tear that allows blood to flow between the aortic wall layers, causing them to separate. As a result, alongside the original aorta (true lumen), a false lumen (FL) develops. TBAD compromises the whole cardiovascular system, in the worst case resulting in complete aortic rupture. Clinical studies have shown that dilation and rupture of the FL are related to the failure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…( 2022 ), as well as in a recent study by Jafarinia et al. ( 2022 ) it was found that it is possible to predict the FL thrombosis using a rigid wall assumption for patient-specific cases. To validate the results, clinical research is needed to understand the role of morphology in predicting FL thrombosis.…”
Section: Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…( 2022 ), as well as in a recent study by Jafarinia et al. ( 2022 ) it was found that it is possible to predict the FL thrombosis using a rigid wall assumption for patient-specific cases. To validate the results, clinical research is needed to understand the role of morphology in predicting FL thrombosis.…”
Section: Limitationsmentioning
confidence: 84%
“…Chong et al (2022) concluded that accounting for the interaction of blood flow with the flap and the wall increases the amount of thrombus in the FL by 25 %. However, in previous studies of , Menichini et al (2018), Armour et al (2020), andArmour et al (2022), as well as in a recent study by Jafarinia et al (2022) it was found that it is possible to predict the FL thrombosis using a rigid wall assumption for patient-specific cases. To validate the results, clinical research is needed to understand the role of morphology in predicting FL thrombosis.…”
Section: Limitationsmentioning
confidence: 94%
“… 2020 ; Jafarinia et al. 2022 ). In these studies, the effect of thrombus breakdown induced by high shear stress was neglected, which could result in overpredictions of thrombus volume.…”
Section: Discussionmentioning
confidence: 99%
“… 2022 ; Jafarinia et al. 2022 ), a lower threshold of shear strain rate (10 s -1 ) was adopted in BFS simulations to avoid overpredictions over the step, but a value of 50 s -1 was used in patient-specific thrombosis modeling for both accuracy and computational efficiency. In this study, we chose the same shear rate threshold of 50 s -1 in all simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue exposed to elevated TAWSS for an extended period has a higher likelihood of rupture, 85,86 whereas low TAWSS is likely to promote risk of endothelial cell degeneration and serves as a key activator in thrombus formation. [81][82][83] The TAWSS is evaluated for the seventh cardiac cycle adopting the RWA, E90, and gHGO models and compared in Figure 11. In all three models, areas of elevated TAWSS are found in the ascending aorta, in the true luminal arch region, near branching vessels, and in the iliac arteries due to their pronounced curvature.…”
Section: Shear Stress-based Indicatorsmentioning
confidence: 99%